Awareness about Sexually Transmitted Infections and Human Immunodeficiency Virus Infection among Patients with Genital Symptoms - Madhu Gyawalee; BP Paudyal; DB Pokhrel (Nepal Journal of Dermatology, Venereology & Leprology)
Introduction: Sexually transmitted infections (STIs) are a major cause of public health problem. In developing countries, human immunodeficiency virus (HIV) infection is spreading rapidly, with sexually transmitted infections acting as a cofactor for the spread of HIV. Yet adequate awareness regarding these infections is lacking.